Empowering Communities Through Old Oil Wells: Analyzing Legal Frameworks and Policy Gaps in Indonesia - Febriani, Indah; Safa’at, Rachmad; Istislam, Istislam; Qurbani, Indah Dwi (Faculty of Law, Sriwijaya University, Indonesia, 2025)
This article examines the relationship between the operation of old oil wells, as governed by Minister of Energy and Mineral Resources Regulation Number 1 of 2008, and the improvement of community welfare, particularly for communities surrounding mining areas. The regulation aims to empower communities by enabling their participation in oil well operations through Village Unit Cooperatives (KUD) and Regionally Owned Business Entities (BUMD). Employing a socio-legal approach, this study conceptualizes law as a functional social institution and investigates its application in three sub-districts in Musi Banyuasin Regency, South Sumatra Province. The findings reveal that the regulation is ineffective due to its complex permit requirements, which are perceived as a significant obstacle by local communities, thereby impeding its objectives. Moreover, the regulation lacks explicit legal provisions to address community welfare by exploiting old oil wells. To address these shortcomings, the study recommends revising the regulation to simplify licensing procedures and include explicit provisions that promote community welfare. Additionally, it emphasizes the need for policy instruments, such as legal assistance, mentoring, technical and non-technical guidance, and continuous supervision, to support community-led mining activities. These measures are essential to ensure that the operation of old oil wells contributes meaningfully to the welfare of local communities, aligning with the regulation's intended goals.